2021
DOI: 10.1101/2021.08.01.21261297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic and mucosal IgA responses are variably induced in response to SARS-CoV-2 mRNA vaccination and are associated with protection against subsequent infection

Abstract: Vaccines against SARS-CoV-2 administered via the parenteral route (intra-muscular = i.m.) are effective at preventing COVID-19 in part by inducing neutralizing antibodies in the blood. The first line of defense against SARS-CoV-2 is in the upper respiratory tract, yet we know very little about whether COVID-19 vaccines induce immunity in this compartment, if at all. We analysed salivary antibodies against the SARS-CoV-2 Spike protein and its receptor binding domain (RBD) following 2 i.m. injections of either B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…We found that these vaccines generated neutralizing activity in the saliva comparable to natural infection, with peak levels after the second dose in those individuals which had high levels of IgA in their saliva as determined by ELISA. The SPIKE and RBD binding IgA antibodies in these samples were shown to have secretory component as would be expected of dimeric IgA in the saliva (44), and importantly, dimeric IgA has been shown to be a more potent neutralizer than either IgG or monomeric IgA (55).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We found that these vaccines generated neutralizing activity in the saliva comparable to natural infection, with peak levels after the second dose in those individuals which had high levels of IgA in their saliva as determined by ELISA. The SPIKE and RBD binding IgA antibodies in these samples were shown to have secretory component as would be expected of dimeric IgA in the saliva (44), and importantly, dimeric IgA has been shown to be a more potent neutralizer than either IgG or monomeric IgA (55).…”
Section: Discussionmentioning
confidence: 73%
“…In the ELISA assays used by the Gommerman lab to quantify salivary anti-RBD levels, samples were pre-adsorbed with streptavidin to eliminate non-specific streptavidin binding IgA in saliva as previously described (33). The lack of non-specific binding in pre-adsorbed samples is reflected in their low level of IgA signal derived from pre-COVID-19 saliva (data not shown, please see accompanying manuscript) (44). Maximum infection and FRNT50 quantification of neutralizing activity in 1dose and "A Low'' 2-dose groups all had significantly higher neutralizing activity compared to Baseline (Figures 4D, 4E), as well as comparable neutralizing activity to convalescent saliva collected by OraSure (Figures 1G, 1H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Additionally, IgA and IgG neutralising antibodies, including highly effective secreted dimeric IgA, have been observed in the saliva of patients vaccinated with BNT162b1 or mRNA-1273. 15,[18][19][20] These studies show variable capacity among the parenteral vaccines to induce sterilising immunity at the mucosa, with ChAdOx1 vaccine being potentially less effective than the mRNA vaccines. Factors potentially influencing whether these vaccines induce mucosal sterilising immunity include the mechanism of the vaccine and the quantity and quality of circulating neutralising antibodies generated.…”
Section: Mechanisms Limiting Sars-cov-2 Infection and Replication Induced By Vaccination Effect Of Sars-cov-2 Vaccination On Infectionmentioning
confidence: 94%
“…Therefore, studies detecting IgA in addition to IgG in saliva will help to better understand the dynamics of COVID-19 mucosal immunity. Thus, saliva antibody assays could be valuable to monitor vaccine take and correlates of protection when inhaled or intranasal boosters become available [34].…”
Section: Discussionmentioning
confidence: 99%